Investigating the impact of pre-slaughter management factors on meat quality outcomes in cattle raised for beef: A scoping review - Sullivan, Paxton; Davis, Melissa; Bretón, Jimena; Edwards-Callaway, Lily (Frontiers in Animal Science, 2022)
The pre-slaughter management period is a critical juncture in the beef supply chain, having implications not only for animal welfare and product quality, but also for profitability. During this period, cattle are exposed to many stressors in a short time, many of which have been shown to impact meat quality. Understanding how cattle management during this terminal step in the production chain affects meat quality and economic outcomes is crucial. The objective of this study was to investigate, synthesize, and report on research evaluating the impact of management factors during the pre-slaughter period on beef quality. A systematic approach was used to search for peer-reviewed and primary studies published in English in CAB Abstracts, PubMed, and Web of Science. A total of 3,217 non-duplicate records were screened for eligibility; articles were deemed eligible for inclusion if they included beef cattle in the pre-slaughter period and reported at least one meat quality outcome. After three screening rounds, 85 articles met all inclusion criteria. Data pertinent to the scoping review’s aims were extracted, including study location, population characteristics, pre-slaughter factors reported, and outcomes of interest. Europe (35, 41%) and South America (21, 25%) represented approximately two-thirds of the studies. Bulls (37, 43.5%) and steers (34, 40.0%) were the most reported sex classes, with the most frequent breed types reported as predominantly British or Continental and Bos indicus breeds (24, 28.2%; 24, 28.2%, respectively). Transportation (n=46), lairage (n=36), and handling (n=35) practices were the most reported pre-slaughter factors. Overall, 59 studies reported pH as an outcome of interest – almost double that of the next highest outcome, bruising (n=35). Muscle pH was most assessed with predictors at the abattoir (n=37); conversely, the effects of transportation were most evaluated on bruising (n=23). A consistent trend across all the categories was that there were relatively few studies evaluating the impact of pre-transport factors on meat quality. Charting the relevant literature is a critical step towards understanding the relationship between pre-slaughter management and end-product quality; doing so will help industry stakeholders in the beef production chain optimize management practices that improve meat quality and enhance profitability.